Applying 3D measurements and computer matching algorithms to two firearm examination proficiency tests. (February 2017) - Ott, Daniel; Thompson, Robert; Song, Junfeng
Graphical abstract: Highlights: Computer aided visual comparisons are presented for 2D and 3D images of evidence. A connection between visual comparisons and quantifiable similarity metrics is made. Visualization tools that support the presentation of firearms evidence are presented. A common proficiency test is analyzed using a computer comparison algorithm. The CMC method successfully passes proficiency tests from two different years. Abstract: In order for a crime laboratory to assess a firearms examiner's training, skills, experience, and aptitude, it is necessary for the examiner to participate in proficiency testing. As computer algorithms for comparisons of pattern evidence become more prevalent, it is of interest to test algorithm performance as well, using these same proficiency examinations. This article demonstrates the use of the Congruent Matching Cell (CMC) algorithm to compare 3D topography measurements of breech face impressions and firing pin impressions from a previously distributed firearms proficiency test. In addition, the algorithm is used to analyze the distribution of many comparisons from a collection of cartridge cases used to construct another recent set of proficiency tests. These results are provided along with visualizations that help to relate the features used in optical comparisons by examiners to the features used by computer comparison algorithms.